PEMANFAATAN REFERENCE MANAGEMENT SOFTWARE (RMS) UNTUK PENYUSUNAN KARYA ILMIAH DI PERGURUAN TINGGI - mufid mufid (IAIN Ponorogo, 2014)
Reference management software (RMS) is useful application for researchers, lecturers and students helping them to compose scientifc paper. This software has fuctioned to search online scientifc information, to save search results, and to write bibliography, includes making citation and references automatically, to facilitate to share references with other users and to sincron references web based on desktop or mobile phone.This article tries to introduce RMS. Using RMS, error on writing citation and references can be avoided, publishing of scientifc works would be increased and more qualifed.